2021
DOI: 10.1111/jfd.13522
|View full text |Cite
|
Sign up to set email alerts
|

Mortality patterns during the freshwater production phase of salmonids in Norway

Abstract: The Norwegian aquaculture industry is continuously growing, and sales of Atlantic salmon (Salmo salar) smolts increased from 288 million in 2011 to 372 million in 2019. Sales of rainbow trout (Oncorhynchus mykiss) smolts increased from 20 to 28 million in the same period (NFD, 2021b) (Figure 1). The industry is highly regulated, including animal welfare (Gismervik et al., 2020). However, it is still challenging to assess and benchmark fish welfare. Fish are held in an environment that is difficult for humans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Pathogen screening of 27 pink salmon in Gulf of Alaska (GoA) during the winter of 2019 demonstrated that they are carriers of several opportunistic and pathogenic species (Deeg et al, 2022). The opportunistic bacterium Candidatus Branchiomonas cysticola seems to be ubiquitous and highly prevalent in pink salmon in the Pacific and native salmonids in Norway (Garseth, Florø‐Larsen, et al, 2020; Gåsnes et al, 2019; Lennox et al, 2020). The bacterium has also been detected in pink salmon in Norway (Fjær, 2019).…”
Section: Synthesizing Pink Salmon Knowledge Between Pacific and Atlanticmentioning
confidence: 99%
“…Pathogen screening of 27 pink salmon in Gulf of Alaska (GoA) during the winter of 2019 demonstrated that they are carriers of several opportunistic and pathogenic species (Deeg et al, 2022). The opportunistic bacterium Candidatus Branchiomonas cysticola seems to be ubiquitous and highly prevalent in pink salmon in the Pacific and native salmonids in Norway (Garseth, Florø‐Larsen, et al, 2020; Gåsnes et al, 2019; Lennox et al, 2020). The bacterium has also been detected in pink salmon in Norway (Fjær, 2019).…”
Section: Synthesizing Pink Salmon Knowledge Between Pacific and Atlanticmentioning
confidence: 99%
“…The availability of monthly data on fish mortality during the freshwater phase presents an opportunity for further investigations that integrate fish from hatcheries into the SyS system. However, the feasible use of this data is hindered by the lack of proper identification of fish that belongs to specific cohorts, which arises from common practices in hatcheries involving grading and movement of fish between tanks [57]. For diseases that can occur at any point during seawater production, alarm delays are a consequence in younger fish.…”
Section: Discussionmentioning
confidence: 99%
“…Low thiamine in steelhead is an additional stressor on already struggling populations. A major factor that affects fish survival in hatcheries is infectious disease [ 26 , 46 ]. Thiamine deficiency contributes to T-cell-dependent and -independent immune dysfunction [ 47 ], as well as lowered WBC bactericidal activity and the mitogenesis of fish cells in vitro [ 48 ].…”
Section: Discussionmentioning
confidence: 99%